Superação do psicologismo por meio da Epoché nos textos husserlianos de 1906/7 - Andrade, Caio Augusto de (2013)
The objective of this study is to show how Husserl overcame psychologism through epoché, from lessons given in the year 1906/7 at the University of Göttingen, that are posthumously published as the title: Introduction to Logic and Theory of Knowledge and The Idea phenomenology. The study on the epoché is justified by the fact that it is the determining methodological element for the change in thinking of Husserl between the publication of the Logical Investigations (1900/1) and Ideas for a pure phenomenology and phenomenological philosophy (1913). This methodological element provided three changes: the passage of conception of phenomenology form descriptive psychology to science of pure consciousness; the distinction between immanence reell and immanence real, and the more accurate understanding of the motivating factor and the various forms of psychologism. This study presents the following hypothesis: epoché overcome psychologism, suspending all transcendent knowledge consciousness by giving it an index of questionableness. This suspension permits that cogitations, which are genuinely (reell) immanent to consciousness, are the unquestioned starting point to phenomenological research of the purely intuitive given. The result of this study allows to distinguish the epoché of Cartesian methodical doubt and to delimit the understanding Husserl's Theory of Knowledge and Philosophy First and as critique of reason